(untitled) (CIPEEX, 2025)
The internal anatomy of root canals presents a challenge to overcome during endodontic treatment. However, the knowledge and experience of the professional, combined with complementary exams, help in resolving complex cases. The purpose of this report is to describe a clinical case based on the endodontic treatment of a maxillary premolar with three canals. A 47-year-old male patient was referred by another professional who, during coronal access, was unable to locate the root canal. Therefore, in addition to periapical radiography, a cone-beam computed tomography (CBCT) was requested, confirming the presence of three root canals in tooth 25 and a diagnosis of asymptomatic apical periodontitis. A margin elevation was performed due to the significant coronal destruction present, and the endodontic treatment was carried out following a sanitization protocol starting with coronal opening, root canal debridement, apical third preparation with the Wave One Gold reciprocating system up to a medium file (35/0.6), supplementary protocol for irrigant agitation with EasyClean, intracanal medication with UltraCal, and subsequently obturation with the lateral condensation technique using Wave One Gold gutta-percha cones and AhPlus sealer. The success of endodontic treatment also depends on accurate diagnosis and planning, effective sanitization, shaping, and obturation.